Great Sand Dunes National Monument - Petersen, David (New York Children's Press, 1999)
Describes the history, landscape, wildlife, and available activities of Great Sand Dunes National Monument
"Organizations and online sites": p. 45
Includes bibliographical references (p. 44) and index
Hurg
5 8
Keywords: National monuments; Great Sand Dunes National Park and Preserve